Finger vein verification - Krishna Veni, Selvan. (Universiti Malaysia Sarawak, UNIMAS, 2009)
At present, biometric system is well - liked as its high security level manage to reduce frauds, intrudes and forgeries. A biometric system utilizes physiological features and behavior characteristics of an individual such as face, finger mark, iris, handwriting, voice, signature and others. One of the recent biology feature used as biometric system is the finger vein. The vein features are robust, stable and most importantly unique for every individual. This trait offers a higher security because for gery is extremely difficult. The finger vein verification project verifies a person‟s identity based on the vein patterns. Generally, the finger vein images are pre - processed and a neural network algorithm is developed to verify the finger vein images. Las t but not least, the performance of the finger vein verification is evaluated. The project achieved an overall accuracy of 82.86%.